2015
DOI: 10.1038/srep11169
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Photon Switch Assisted by Coupled Quantum Dots

Abstract: Quantum switch is a primitive element in quantum network communication. In contrast to previous switch schemes on one degree of freedom (DOF) of quantum systems, we consider controlled switches of photon system with two DOFs. These controlled photon switches are constructed by exploring the optical selection rules derived from the quantum-dot spins in one-sided optical microcavities. Several double controlled-NOT gate on different joint systems are greatly simplified with an auxiliary DOF of the controlling ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
(187 reference statements)
0
6
0
Order By: Relevance
“…Thus our four Toffoli gates are deterministic and faithful. However, the side leakage from the cavity is unavoidable in the experiment [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. In this case, the reflectance coefficients r 0 and r h are shown in figure 7.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus our four Toffoli gates are deterministic and faithful. However, the side leakage from the cavity is unavoidable in the experiment [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. In this case, the reflectance coefficients r 0 and r h are shown in figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, implementation of a Toffoli gate requires six CNOT gates and 10 single-qubit operations [19]. In recent years, Ralph et al [20], Lanyon et al [21] and Luo et al [22] have demonstrated a general technique that harnesses multi-level information photonic carriers to realize a three-qubit Toffoli gate with reduced CNOT gates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This architecture may be a good candidate to distribute quantum information over a long distance. In experiment, the QED has been applied to generate photonic entanglements [38][39][40], transmit quantum states between light and a single trapped atom [41,42], or provide the photon routers [43][44][45]. The strong coherent interactions between atoms and photons have inspired lots of researches in quantum information processing [46][47][48].…”
Section: Introductionmentioning
confidence: 99%